A Single Institutional Experience With the Paris System for Reporting Urinary Cytology: Correlation of Cytology and Histology in 194 Cases. Issue 2 (6th June 2018) - Zare, Somaye; Mirsadraei, Leili; Reisian, Niloufar; Liao, Xiaoyan; Roma, Andres; Shabaik, Ahmed; Hasteh, Farnaz
Abstract: Objectives: The Paris System for Reporting Urinary Cytology (TPS) is designed to standardize the criteria and terminology used in urinary tract cytology reporting. The aim of this study was to evaluate the impact of implementing TPS and to analyze the correlation with follow-up biopsies in order to assess its reproducibility. Methods: Urinary tract cytology specimens with follow-up biopsies over a 2-year period were reviewed and reclassified according to TPS criteria. Surgical follow-up diagnoses were correlated with the initial cytology diagnoses and TPS interpretations, and the results were compared. Results: Applying TPS in comparison to our previous reporting system resulted in fewer cases in the atypia category (11.8% vs 24.2%) and higher specificity, accuracy, and predictive value. We observed acceptable interobserver agreement in diagnostic categories of this reporting system. Conclusions: TPS improves the overall performance of urinary tract cytology by standardizing the criteria and terminology.